An Extramural English Language Course For Snorkeling Guides In North Lombok, West of Nusa Tenggara - Jumadil; Sri Sukarni; Agus Salim; Ahmad Hanan; Taufik Suadiyatno (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
These problems gave birth to opinions about why certain tourism actors, particularly those who offer snorkeling at Nara Bay, Malaka Village, North Lombok Regency, are unable to learn English and excellence service. If we go deeper, we find that the lack of exposure to English and English is the main cause of the issue. The scarcity of English language training facilities that offer opportunities for language exposure poses a challenge for local tourism players. This activity uses mentoring and training for English language proficiency as well as guiding strategies for Snorkeling Guides. At the end of the training, 100% of participants used the language function in accompanying tourists and 100% had mastered guiding techniques in accordance with existing procedures such as explaining each function of snorkeling equipment, explaining how to breathe using a mask and demonstrating how to enter the water and swim using a mask. Snorkel your advice visitors not to handle potentially harmful marine life.